PERALIHAN HAK ATAS TANAH ABSENTE KARENA WARIS (STUDI KASUS DI KANTOR ATR/BPN KABUPATEN KENDAL YANG DOMISILI AHLI WARIS BERADA DILUAR WILAYAH KECAMATAN ) - Ika Rahma Wanti; Munsyarif Abdul Chalim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
The law states that if a person has an excess of absent land then the land must be released or the sanction will be imposed. In fact, although this prohibition applies, the ownership or control of agricultural land in absente or drags is found in many sub-districts in kendal district, in the kendal district, there are many owners of agricultural land owned by persons or legal entities that are not only outside the kecamatan but sometimes Outside areas such as, Semarang city, and even those who are domiciled outside the province.The problems studied in this study are as follows: (1) how the concept of transition of absente land rights due to the heirs whose domicile heirs are outside the district area, (2) how the legal protection for the heirs of absente land owners who live outside District area.This study uses empirical juridical approach, empirical juridical approach in this research means that in analyzing the problem is done by combining legal materials (which is secondary data) with primary data obtained in the field.The results of this study indicate the following: (1) The ownership of Asbsentee land rights due to inheritance issues the right to the heirs to obtain the rights to the absentee land, and for the transition of absentee land to legal certainty, (2) Protection for the heirs of land owners Absentees residing outside the sub-district may occur if the inheritance has been in accordance with the legislation in the true sense of being the heir of the absentee landowner and the heirs residing outside the sub-district work on their own farmland.Keywords: Absente Land / Guntai, Heirs, Land Rights Transfer.